(untitled) (European journal of volunteering and community-based projects, 2024)
The paper highlights New York City’s post-pandemic resilience while summarizing its budgetary situation for 2023. Despite persistent inequality, the 8.34 million-person city maintains its economic strength and diversity. Real estate taxes accounted for 110.3 billion of total receipts, while social services and education accounted for 106.8 billion of expenses. Sustainability, social justice, and public safety are important policy priorities. To ensure long-term stability, the city places a strong emphasis on budgeting and strategic investments.